Analisis Hak Anak Terhadap ASI (Air Susu Ibu) Dalam Konteks Pendidikan Karakter Islami - Saiyidah, Luthfia Hanifatus; Al Najla, Nabila; Erlina, Erlina; Ghazi, Fachrul; Kholid, Idham (Universitas Muhammadiyah Magelang, 2025)
Breast milk (ASI) not only serves as a source of nutrition for infants but also functions as a means of building emotional bonds and instilling moral values from an early age. In the Islamic perspective, breastfeeding receives special attention as reflected in the sources of Sharia and socio-religious practices. This article aims to analyze the ethics of motherhood in Islam concerning the fulfillment of children’s rights to breast milk and its implications for Islamic character education. The research method employs library research and normative analysis of religious literature, health policies, and recent empirical studies. The findings indicate that Islamic traditions and laws encourage the fulfillment of children's rights to receive exclusive and continued breastfeeding; however, its implementation is often influenced by social, cultural, and healthcare system factors. The concept of maternal ethics in Islam, which emphasizes compassion, responsibility, and exemplary behavior, can be integrated into character education curricula to promote broader breastfeeding practices. Recommendations include strengthening family education based on Islamic values, implementing breastfeeding-friendly school policies, and developing integrated counseling programs involving religious leaders and health practitioners.